Evolution of a rock slope failure at Skredkallen, Vannøya - Mikkelsen, Martin (UiT Norges arktiske universitet, 2019)
Rock slope failures are known major contributors to landscape evolution in alpine Norway, and also pose a threat to people and infrastructure in the present day. By examining the history of rock slope failures at active rockslide sites an understanding of recurrence intervals and triggering mechanisms can be achieved. The focus of this study is to form a complete picture of the evolution of an area of Vannøya, Troms, where an unstable slope sits above large failure deposits indicative of a sequenced failure history. The deformation of the URS, geomorphology of the area and geochronology of the deposits has been examined to provide a context and timing for the failure evolution of the slope and the larger area. Skredkallen is a 1.1 Million cubic meters actively deforming unstable rock slope (URS) located on the steep E-facing slope of Laukvikfjellet on Vannøya. Sitting at the base of the unstable slope is a c. 13 Million cubic meters rock avalanche deposit, stretching to 1.4 km from the unstable area, and consisting of blocks ranging in size up to c. 1000 cubic meters. Morphostructural mapping suggests a biplanar compound slide (dominated by more than one sliding surface) formed by a step-path geometry between the gently-dipping foliation and steep joint sets. A prominent column (Kallen), controlled by orthogonal joints, formts the outer boundary of the URS and is toppling at c. ≤12 mm/yr towards the E. Deglaciation of the area occurred 15 – 13 ka, followed by isostatic rebound and relative sealevel changes, resulting in three prominent shorelines. The failure deposits are characterized by 3 domains (inner, middle and outer) by geometry and runout distance. The two outermost domains show evidence of marine erosion and deposition at elevations consistent with the Main and Tapes shorelines. 14C dating of a lake sediments on top of the inner domain revealed an age of 1642 cal. yr BP. These relative timing constraints suggest a rock avalanche or series of avalanches occurring between the formation of the marine limit ...